2019
DOI: 10.1039/c8tb01676c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient capture and photothermal ablation of planktonic bacteria and biofilms using reduced graphene oxide–polyethyleneimine flexible nanoheaters

Abstract: A flexible nanoheater device, consisting of a Au nanohole array coated with reduced graphene oxide–polyethyleneimine, was applied to capture and eradicate both Gram-positive and Gram negative planktonic bacteria and their biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Upon GO reduction using hydrazine (refer to the SI for details), the intensity of vibrations related to oxygen functional groups are reduced significantly while the C--C vibration is blue-shifted to 1604 cm − 1 . These results clearly indicate GO reduction to rGO and restoration of the aromatic network, in accordance with our previous results [36].…”
Section: Characterization Of Cos-rgosupporting
confidence: 93%
“…Upon GO reduction using hydrazine (refer to the SI for details), the intensity of vibrations related to oxygen functional groups are reduced significantly while the C--C vibration is blue-shifted to 1604 cm − 1 . These results clearly indicate GO reduction to rGO and restoration of the aromatic network, in accordance with our previous results [36].…”
Section: Characterization Of Cos-rgosupporting
confidence: 93%
“…6). This is in accordance with our previously obtained results for the coating of rGO and polyethyleneimine [18]. Also, previous studies of our colleagues from the group showed that the exfoliated graphene and GO did not have antibacterial properties [25,26], and they did not produce singlet oxygen, which is usually responsible for antibacterial activity of GO [27].…”
Section: Antibacterial Activity Of K/rgo-cs Interfacesupporting
confidence: 93%
“…However, recently, it has attracted the attention of many researchers for biological applications, including biosensors, tissue engineering, and the design of antibacterial materials [11][12][13][14]. In order to improve the antibacterial activity of graphene, some research groups have prepared its nanocomposites with different polymers such as chitosan [15,16], polyamide [17], polyethyleneimine (PEI) [18] or poly(vinyl alcohol) [19]. Chitosan is a cationic biopolymer derived from chitin, with promising antimicrobial properties, excellent biocompatibility and biodegradability [20].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of materials were reported to generate heat that was sufficient to kill different types of bacteria in planktonic or biofilm cultures. Kim, et al, found that excitation of catechol-conjugated poly(vinylpyrrolidone) sulfobetaine linked to polyaniline by NIR laser caused temperature elevation (52–55 °C) that was efficient to kill Staphylococcus aureus and Escherichia coli after 3 min of NIR excitation [70]. Moreover, NIR laser excitation of graphene oxide-polyethyleneimine nanoheaters resulted in temperature elevation of more than 50 °C, that was capable to kill Staphylococcus aureus and Escherichia coli bacteria, in addition to Staphylococcus epidermidis bacterial biofilm [71].…”
Section: Resultsmentioning
confidence: 99%